If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-(8+2X)=-16
We move all terms to the left:
X-(8+2X)-(-16)=0
We add all the numbers together, and all the variables
X-(2X+8)-(-16)=0
We add all the numbers together, and all the variables
X-(2X+8)+16=0
We get rid of parentheses
X-2X-8+16=0
We add all the numbers together, and all the variables
-1X+8=0
We move all terms containing X to the left, all other terms to the right
-X=-8
X=-8/-1
X=+8
| -1x+20=12 | | 6+0.10x=15x+10 | | F(6)=6x+3 | | I*z^2+2*z-1=0 | | 72x+300=30(240+1500) | | 6.44=-4.6(x-3.8) | | 4*x-8+3*x+2=180 | | 8(3x-12)=24 | | 15+(-4y)+1=0 | | 11h+4(-6h−18)=9−4h+18 | | -12=l+24 | | -5(2x+3)=5 | | (6w-8)=208 | | 251=-v+156 | | 6(w-8)=208 | | -w+217=100 | | 64=288-u | | 9x-(5x-11)=47 | | 3x-28+3x-30=x | | -9(x-10)=81 | | w(-3)=7 | | 2x+72=8(×+9)-6x | | 8n-(49+7)=13 | | (5x+50)-15=150 | | -8.5x+0.85=-2.55 | | 4x-(9x+4)=-19 | | 75(2x-4=2(x+1) | | 2/5y-7=12 | | 6(9x)=10x-2 | | Z=y/3-3 | | 12^-4x=3 | | 4t-5t÷9=5t-9 |